The Aesthetic Expression of Abstract Calligraphy: Emotion and Form between Brush and Ink - Hou, Yi (Journal of Ecohumanism, 2024)
Calligraphy is one of the most important visual art forms inherited from China for thousands of years. The visual formal resources contributed by the dots and structures of Chinese calligraphy are one of the wonders in the world art history. Among them, abstract calligraphy, as a unique art form, contains rich emotional expression and formal aesthetic exploration between brush and ink. This study adopts a qualitative research paradigm, through in-depth interviews with senior abstract calligraphers, art critics and scholars, combined with on-site observation of the creative process of calligraphy, literature analysis and interpretation of works, in order to comprehensively analyze the emotional connotation and formal vocabulary of abstract calligraphy, and to clarify the intrinsic connection and tension between the two. The results of the study show that in abstract calligraphy, the subject's emotional experience is the root power of modeling. Through the refinement and sublimation of life experience, the calligrapher injects the vibration of individual consciousness and philosophical thoughts into the brush and ink with the help of visual elements such as brush strokes, lines, and compositions. The brush and ink become the direct speech of the mind, and the viewer can feel the rhythm and bitterness of life, the struggle and emptiness of desire, the pursuit of tranquility and other rich emotional experiences in the works. At the same time, the careful construction of formal language is also the core of abstract calligraphy exploration. Through the mastery of brush and ink materials and writing momentum, the use of wet and dry contrast, white space, texture and other techniques, to create a shocking visual tension, giving people a strong experience of formal aesthetics. The study emphasizes that abstract calligraphy realizes a high degree of unity between emotion and form. On the one hand, the form itself carries the spiritual experience and inner emotion of the calligrapher; on the other hand, the emotion gives life and inner tension to the form. The two integrate and echo each other, forming an organic whole. It is this perfect combination of mind and form that makes abstract calligraphy become the visualization of human emotion and spiritual world, and triggers endless thoughts and resonance in the viewers. The researcher comprehensively analyzes the emotional core and formal qualities of abstract calligraphy from both theoretical and empirical levels, providing a new perspective for a deeper understanding of the unique aesthetic value of this art form.